2010 IEEE International Conference on Acoustics, Speech and Signal Processing 2010
DOI: 10.1109/icassp.2010.5495580
|View full text |Cite
|
Sign up to set email alerts
|

Noise robust exemplar-based connected digit recognition

Abstract: This paper proposes a noise robust exemplar-based speech recognition system where noisy speech is modeled as a linear combination of a set of speech and noise exemplars. The method works by finding a small number of labeled exemplars in a very large collection of speech and noise exemplars that jointly approximate the observed speech signal. We represent the exemplars using melenergies, which allows modeling the summation of speech and noise, and estimate the activations of the exemplars by minimizing the gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 11 publications
3
75
0
Order By: Relevance
“…Furthermore, applications of NMF in audio processing are not limited to BSS, as there is a growing number of studies showing the advantage of NMF-based audio feature extraction, especially in noisy conditions [6][7][8]. On the other hand, with the increasing amount of computational power available today even on mobile devices, we are moving towards the point where NMF-based algorithms are ready to be used in real-life applications.…”
Section: Background and Objectivesmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, applications of NMF in audio processing are not limited to BSS, as there is a growing number of studies showing the advantage of NMF-based audio feature extraction, especially in noisy conditions [6][7][8]. On the other hand, with the increasing amount of computational power available today even on mobile devices, we are moving towards the point where NMF-based algorithms are ready to be used in real-life applications.…”
Section: Background and Objectivesmentioning
confidence: 99%
“…Consequently, it receives increasing attention at the moment [6]. Thereby different sets of components are selected as an in-or overcomplete feature basis, for which the time-varying activation matrix (i. e., the second NMF factor) is computed by supervised NMF.…”
Section: Supervised Nmf and Acoustic Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…models which describe the magnitude spectra of complex sounds as being composed of a purely additive (no negative components) combinations of spectral atoms, have proven to be adept at separating the target speech from interfering sounds such as noise [1,2], other speakers [3,4], music [5,6,7] and even reverberation [8]. For noise-robust automatic speech recognition (ASR), such compositional models really excel when the atoms also have some temporal extent [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The techniques needed to build a noise-robust system based on the compositional model have been explored in previous work. In [2], we proposed the use of speech and noise exemplars as dictionary atoms and showed that it is possible to directly map the sparse weights of the clean speech atoms to state posteriors. In a feature enhancement method [9], the compositional model is used to obtain clean speech and noise estimates which are in turn used to define a Wiener filter.…”
Section: Introductionmentioning
confidence: 99%